2008
DOI: 10.1007/s11270-008-9703-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fiber Additives on the Desiccation Crack Behavior of the Compacted Akaboku Soil as A Material for Landfill Cover Barrier

Abstract: In the daily and final landfill cover barrier system, the hydraulic properties of compacted soil liners and the strength of soil can be adversely affected by desiccation cracking, resulting in the loss of effectiveness and integrity of the containment system as a barrier. Recently, there is an interest of using fiber additive to overcome the desiccation cracking problem. In this study, the desiccation crack test was conducted to investigate the effect of fiber additive on suppressing desiccation cracks in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 14 publications
0
27
0
1
Order By: Relevance
“…The drying process was carried out at a temperature of about 34 卤 2 o C for 10 days using an oven with fan. The surface dimensions of cracks were measured using gauge wires to find the crack intensity factor (CIF) to access the magnitude of desiccation cracks that form in the soils, which is written as (Harianto et al 2008;Kleppe&Olson 1985;Peng et al 2006):…”
Section: Volumetric Shrinkage Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The drying process was carried out at a temperature of about 34 卤 2 o C for 10 days using an oven with fan. The surface dimensions of cracks were measured using gauge wires to find the crack intensity factor (CIF) to access the magnitude of desiccation cracks that form in the soils, which is written as (Harianto et al 2008;Kleppe&Olson 1985;Peng et al 2006):…”
Section: Volumetric Shrinkage Testmentioning
confidence: 99%
“…It is also possible, however, for fibers not to effectively fill the pore spaces or come in full contact with soil particles. In such cases, 桑 dmax would decrease (Harianto et al 2008). It could be then that the inclusion of NCs beyond the optimum limit may possibly result from agglomeration of NC filaments.…”
Section: Effect Of Ncs On Compaction Conditionsmentioning
confidence: 99%
“…cement, lime, fibre, fly ash, and silica fume (Akcanca and Aytekin 2012;Al-Rawas et al 2005;Dash and Hussain 2012;Guney et al 2007;Harianto et al 2008;Kalkan 2009;Miller and Azad 2000;Nalbanto臒lu 2004;Rifai 2000;Tastan et al 2011;Walker 1995). In general, these studies have shown that the cracks in the soil can be suppressed but the soil hydraulic conductivity will increase.…”
Section: Introductionmentioning
confidence: 99%
“…They have concluded that reinforcement of expansive soils with discrete polymeric fibers potentially offer an alternative method to chemical stabilization techniques and other methods for reducing swell potential. Harianto et al (2008) studied the effect of fiber on the volume change characteristics and dessication cracking of Akaboku soil as a material for landfill cover barrier. It was observed in this study that the addition of fiber decreased the volume change, and the volumetric shrinkage strain.…”
Section: Introductionmentioning
confidence: 99%